Strategi Kepala Madrasah dalam Meningkatkan Kompetensi Profesionalisme Guru Pendidikan Agama Islam di MA Al Amin Malang - Rahmawati, Rahmawati (Universitas Indraprasta PGRI Jakarta, 2024)
This research aims to reveal the strategies used by the pricipal of Madrasah in increasing the competency and professionalism of Islamic religious education teachers at MA Al Amin Malang. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with the principal, observations, and analysis of related documents. The research results show that the Principal of Madrasah use various strategies, including continuous training and development, providing support and recognition, as well as ongoing coaching and supervision. These strategies aim to improve the quality of teaching and learning, inspire teacher motivation, and strengthen commitment to the profession. The implications of this research are the important role of the Principal in creating a work environment that is conducive to developing teacher professionalism, as well as the need for investment in ongoing training and coaching. This research was conducted over a period of time from July to December 2023. It is epected that this research can provide valuable input for the development of more effective school management policies and practices in Islamic religious education institutions.